2015
DOI: 10.1245/s10434-015-4814-7
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Potential of Preoperative Nutritional Status in Long-Term Outcome Projections for Patients with Gastric Cancer

Abstract: Preoperative PNI may have merit as a gauge of prognosis for patients with GC at stages 1 and 2, but PNI and postoperative morbidity showed no correlation in this setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
82
1
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(96 citation statements)
references
References 27 publications
7
82
1
6
Order By: Relevance
“…In our practice, a detailed preoperative nutritional assessment is performed to determine the potential malnutrition in patients with gastric cancer (9,10). In addition to simple anthropometric measurements (e.g., weight, body mass index, weight loss ratio, and Nutritional Risk Screening (11).…”
Section: Management Of Locoregional Diseasementioning
confidence: 99%
“…In our practice, a detailed preoperative nutritional assessment is performed to determine the potential malnutrition in patients with gastric cancer (9,10). In addition to simple anthropometric measurements (e.g., weight, body mass index, weight loss ratio, and Nutritional Risk Screening (11).…”
Section: Management Of Locoregional Diseasementioning
confidence: 99%
“…Preoperative PNI is hypothesized to be a prognostic marker for a number of malignancies, including long-term survival for patients with GC (10,11,17,45). However, no association between either preoperative or postoperative PNI and survival in patients with GC who received S-1 ACT was demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic significance of a number of clinical parameters has been examined for patients with GC subsequent to radical surgery (8)(9)(10)(11)(12)(13)(14)(15). Of these, the preoperative prognostic nutritional index (PNI) as a reflection of the immunological and nutritional condition of the patients has been associated with the outcomes of patients who undergo gastrectomy for a number of stages of GC (10,11,16,17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent meta-analysis, PNI was associated with depth of invasion and lymph node metastasis in GC [29]. Sakurai et al [30] showed that in patients with GC, the preoperative PNI is an independent predictive factor for both overall survival and disease-specific survival. Notably, the patients with UICC stage 1 and 2 disease had significantly worse outcomes in the low-PNI group than in the high-PNI group.…”
Section: Evaluation Of Nutritional Statusmentioning
confidence: 99%